The Effect of Spiritual Emotional Freedom Technique Therapy on Anxiety Among The Coronary Heart Disease Patient Undergo Percutaneous Coronary Intervention - Megasari, Anis Laela; Putri, Noviyati Rahardjo; Setiawan, Ahmad Eri (POLTEKKES KEMENKES PADANG, 2023)
One of the management of coronary heart disease is percutaneous coronary intervention. Percutaneous coronary intervention often causes anxiety in coronary heart disease. Anxiety in coronary heart disease will undergo percutaneous coronary syndrome must intervene because it can have adverse effects such as unstable hemodynamic status. This study aims to determine the effects of SEFT in reducing anxiety in patients with coronary heart. This research used a design of pre-experimental quantitative method with a one-group pre-post test design approach. This research used a saturated sampling method with 30 respondents and was conducted in dr. Moewardi Hospital. SEFT was given to the respondents 15 minutes before percutaneous coronary intervention do. The anxiety of the patient was measured before and after SEFT. Anxiety assesses using the HARS questionnaire. HARS questionnaire has a score of 0-56. The results of this study are the mean score of anxiety decreasing from 28.50 to 20.60 after being given the SEFT intervention. The dependent t-test showed there is an effect of the application of SEFT therapy, it reduces anxiety in coronary heart patients who would undergo percutaneous coronary intervention with a p-value of 0.000. The application Spiritual Emotional Freedom Technique as an alternative to psychotherapy intervention can prevent or reduce anxiety in coronary heart patients who will undergo percutaneous coronary intervention.